Integrated Thinking and Reporting : Focusing on Value Creation in the Public Sector - World Bank Group (World Bank, Washington, DC, 2016)
This introductory guide has been developed by the International Integrated Reporting Council (IIRC), the Chartered Institute of Public Finance and Accountancy (CIPFA) with the support of the World Bank to explain to public sector leaders and their teams how integrated thinking and reporting can help the sector consider how make the most of resources, encourage the right behaviors and demonstrate to stakeholders how they are achieving the strategy and creating value over the short and longer term.